Transcending the Elements: the Meaning in the Mist and Stars in Charles Dickens’s Great Expectations - Stromberg, Isabelle (Meliora, 2021)
In this senior thesis, I seek to explore the meaning of the mist and the stars in Charles Dickens’s Great Expectations. I argue that through observation of the mist and the stars as an entrance point to the text, we as readers are able to expand our discussion of the text to incorporate other fundamental aspects of the story. I open with a contextualization of the mist and the stars in Dickens’ previous works, including Bleak House, Oliver Twist, and Sketches by Boz. I argue that the mist stands as a symbol for Pip’s uncertainty about the future and his place in the world, while the stars represent an inaccessible though alluring clarity and transparency. The mist stands as an obstructing force, and the rising of the mist connotes moments of growth and maturation for Pip. The stars act as the cosmic opposition to the mist, and they are synonymous with Pip’s elusive love interest, Estella. Through a reading of the mist and the stars, we gain a deeper connection to the nuances and foundational themes of Great Expectations.